Unjuk Rasa Versus Menghujat (Analisis Deskriptif melalui Pendekatan Hukum Islam - Rahman, Muhammad Gazali (Hunafa: Jurnal Studia Islamika, 2015)
This paper analyzes the rallies phenomenon versus blaspheming which is analyzed descriptively with the approach of Islamic law. This analysis is then developed in two issues, namely: 1) how the phenomenon of rallies and blaspheming; 2) how the perspective of Islamic law against rallies and blaspheming. While it can not be generalized, the reality of the operations of rallies, obscenities seems to have become anthem should be sung with gusto as the media to berate, inflammatory, blasphemous even less so provoking that leads to anarchy. In fact, the protest phenomenon occurs not only at the level of universities, but also have occurred in institutions of formal education providers’ secondary level (high school or vocational school). Schools are supposed to be the center of the development of a positive culture turned into the arena articulation of words that are very far from polite category.